2020
DOI: 10.1002/adhm.201901783
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti‐Coagulative Nanocomplex in Delivering miRNA‐1 Inhibitor Against Microvascular Obstruction of Myocardial Infarction

Abstract: Great progress has been made in miRNA nanodelivery for the treatment of myocardial infarction (MI). However, miRNA nanodelivery within the infarct is impeded by microvascular obstruction as a local circulatory disorder caused by microthrombus formation in microvessels. Knowing that low molecular weight heparin (LMWH) can effectively prevent microthrombus formation in microcirculation, it is hypothesized whether surface modification of the nanocarrier with LMWH can overcome microvascular obstruction in the infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The mechanism of how Sox4 was regulated in MI also needs to be explored. Some miRNAs have been demonstrated to play a key role in MI, such as miR‐1, miR‐25‐3p, and miR‐21 (Hong et al, 2020; Kang, Kim, Mun, Yun, & Joung, 2020; Peng, Zhao, Peng, Xu, & Yu, 2020). In addition, recent reports describe important regulatory roles for several miRNAs on Sox4 in the cell apoptosis process (D. Li, He, et al, 2018; Yao et al, 2018; Zhao & Ai, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of how Sox4 was regulated in MI also needs to be explored. Some miRNAs have been demonstrated to play a key role in MI, such as miR‐1, miR‐25‐3p, and miR‐21 (Hong et al, 2020; Kang, Kim, Mun, Yun, & Joung, 2020; Peng, Zhao, Peng, Xu, & Yu, 2020). In addition, recent reports describe important regulatory roles for several miRNAs on Sox4 in the cell apoptosis process (D. Li, He, et al, 2018; Yao et al, 2018; Zhao & Ai, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since the physical properties of dendrigrafts are not that different from dendrimers, that is, three-dimensional structures with either a high surface charge, or a chemically decorated surface, the biomedical applications for dendrigrafts do not vary that much from those for dendrimers. The constructs were first considered for gene delivery [ 95 , 96 , 97 , 98 , 99 , 100 , 101 ] and later the focus shifted towards drug delivery [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. Limited work on the use of dendrigrafts in biomedical imaging [ 111 ] was also reported.…”
Section: Poly(amino Acid)-based Dendrigraftsmentioning
confidence: 99%
“…Furthermore, a group constructed a functionalized single-walled carbon nanotube bound to siRNA from caspase 3 (F-CNT-siCas3) that demonstrated good water solubility and biocompatibility, but also had a high transfection efficiency of up to 82%, significantly downregulating the expression of the caspase 3 gene and protein in vivo (124). A low molecular weight heparin-encapsulated exosome nanocomplex demonstrated that it could overcome a microvascular obstruction in the infarct, and this structure not only makes myocardial cells uptake miRNAs, which will promote cardiac repair, but will also prevent myocardiocyte apoptosis and attenuate myocardial fibrosis (125). Although the exosome nanocomplex technology is expensive and holds uncertain side effects, it greatly improves the cell conversion rate compared with the previous two regeneration methods, while showing good in vivo results.…”
Section: Therapeutic Targetsmentioning
confidence: 99%